Prediction of tumor heterogeneity in localized prostate cancer. - Huland, H; Graefen, M; Haese, A; Hammerer, P; Palisaar, J; Pichlmeier, U; Henke, R; Erbersdobler, A; Huland, E; Lilja, H (2002)
Clinical T1 and T2 prostatic carcinoma is a heterogeneous tumor with respect to pathologic stage and outcome. In the authors' experience, 60% of patients have a pT2 prostatic carcinoma, and 2% to 4% have tumors less than 0.5 cm3 in volume. The latter group cannot be predicted by the use of preoperative parameters with a sufficient sensitivity and specificity. Quantitative analysis of six systematic biopsies, that is, reporting the number of biopsies with any Gleason grade 4 or 5 cancer or the number of biopsies with more than 50% Gleason grade 4 and 5 cancer, together with preoperative PSA levels can be used to predict the different pathologic stages and risk groups of patients with T1 or T2 prostatic carcinoma. CART analysis that using these preoperative parameters can predict the lymph node stage and the capsular penetration on each side of the prostate with a sufficient positive and negative predictive value and a sufficient specificity to avoid routine lymphadenectomy in approximately 80% of the patients classified as a low-risk group for having lymph nodes positive for disease. CART analysis also allows a solid identification of patients in whom the unilateral or bilateral nerve may be spared during surgery. These algorithms may be improved further by determining the HK-2 level in the blood or by including other molecular biologic markers in the analysis of the biopsies. Clinical T1 or T2 prostatic carcinoma is a heterogeneous but fairly predictable tumor.